2012
DOI: 10.3109/07388551.2012.672398
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+signals: The versatile decoders of environmental cues

Abstract: Plants are often subjected to various environmental stresses that lead to deleterious effects on growth, production, sustainability, etc. The information of the incoming stress is read by the plants through the mechanism of signal transduction. The plant Ca(2+) serves as secondary messenger during adaptations to stressful conditions and developmental processes. A plethora of Ca(2+) sensors and decoders functions to bring about these changes. The cellular concentrations of Ca(2+), their subcellular localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 167 publications
1
39
0
Order By: Relevance
“…Ahmad et al (2015) demonstrated a higher activity of antioxidant enzymes due to calcium treatment, which contributed to the increased protection of membranes. SOD eliminates superoxide radicals, whereas CAT and APX contribute to radical scavenging by further terminating the superoxide radical generated chain reactions (Siddiqui et al 2012;Sarwat et al 2013;Sofo et al 2016). In our experiments, calcium addition helped plants resist stress and stimulated plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmad et al (2015) demonstrated a higher activity of antioxidant enzymes due to calcium treatment, which contributed to the increased protection of membranes. SOD eliminates superoxide radicals, whereas CAT and APX contribute to radical scavenging by further terminating the superoxide radical generated chain reactions (Siddiqui et al 2012;Sarwat et al 2013;Sofo et al 2016). In our experiments, calcium addition helped plants resist stress and stimulated plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…During stress, the cell cycle progression and cell elongation rates are hindered because stresses exert irreversible effects on membrane potential and the functioning of the proton pumps responsible for cell growth (Karcz & Kurtyka 2007). Calcium protects plants from deleterious impacts of stress by acting in signaling pathways and regulating calmodulinlike proteins to promote several growth mechanisms in plants (Sarwat et al 2013). Ahmad et al (2015) also demonstrated reductions in biomass accumulation in mustard due to cadmium application and its subsequent amelioration by Ca 2+ Note: a, b and c denote significant change among the different treatments in the same parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cADPR-activated Ca 2+ release, plant vacuoles appeared to harbor inositol phosphate-activated Ca 2+ release channels [4,12]. In animals, numerous extracellular stimuli trigger phospholipase C (PLC) activity that catalyzes the cleavage of phosphoinositol-4,5-bisphosphate into diacylglycerol and IP 3 . The IP 3 then binds its receptor which is mainly located on the endoplasmic reticulum (ER), the largest and most controllable intracellular Ca 2+ source in animals, to trigger the elevation of cytosolic Ca 2+ [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all environmental and hormonal signal transduction pathways in plants are associated with a transient increase in cytosolic free Ca 2+ ([Ca 2+ ] cyt ) [3]. [Ca 2+ ] cyt signals can be generated by a Ca 2+ influx from the extracellular space and/or by Ca 2+ release from intracellular compartments, such as the endoplasmic reticulum, mitochondria, chloroplasts, and vacuole [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, other than animals, plants maintain a sessile lifestyle subjected to various environmental stresses (Sarwat et al, 2013). Modern-day plants are all the products of primal livings, and experienced eons of evolution with abiotic and biotic changes.…”
Section: Introductionmentioning
confidence: 99%